The Relationship between Perceived Value and Intentions to Use Drone Food Delivery Services - Muhamad Sukor, Nur Ameeroh; Mohd Nor, Norasmiha (Research in Management of Technology and Business, 2026)
Food delivery services are among the new options in logistics and service delivery made possible by drone technology. Although drone food delivery has been adopted in several advanced countries, Malaysia is currently in the beginning phases of its adoption. For this technology to be successfully used, it is essential to understand the intentions and attitudes of consumers. The purpose of this study is to investigate how perceived value specifically, functional, social, emotional, epistemic, and conditional values relate to Malaysian customers’ intentions to use drone food delivery services. An online questionnaire was used as part of a quantitative research method. Malaysian customers who were at least 18 years old and had previously used food delivery services provided the data. The Statistical Package for Social Sciences (SPSS) was used to analyze 199 valid responses in total. Descriptive statistics were used to measure perceived value and consumer intention, reliability analysis was used to evaluate internal consistency, normality testing was performed, and Spearman’s rho correlation analysis was used to look at correlations between variables. The findings show that consumers’ opinions of drone food delivery services are mostly positive. All five perceived value aspects were shown to have a significant beneficial relationship with consumer intention to use drone food delivery.